Persepsi Tenaga Kerja Lokal Terhadap Penerapan Standar K3 (Keselamatan dan Kesehatan Kerja) pada Proyek Konstruksi di Kabupaten Belu - Bria Seran Malik, Alex; Pereira Maia Pinto, Gaspar (PT Yupin Felicitas Utama, 2025)
This study aims to explore the perception of local workers towards the implementation of K3 (Occupational Safety and Health) standards in construction projects taking place in Belu Regency. With the increasing construction activities in this area, it is important to understand how local workers view and respond to the implementation of K3 standards, which play an important role in maintaining their safety and health in the workplace. The methodology used in this study was a survey with a questionnaire distributed to 100 respondents working in various construction projects in Belu Regency. The data collected were analyzed using descriptive statistical methods to provide a clear picture of the perceptions of local workers. The results of the study indicate that although most local workers are aware of the importance of implementing K3 standards, there are still challenges in its implementation, such as lack of training, adequate facilities, and in-depth understanding of K3 procedures. This study also identified several cases of work accidents that occurred due to non-compliance with K3 standards, which emphasizes the need to increase awareness and training for local workers. Thus, the results of this study are expected to provide recommendations for stakeholders in improving the implementation of K3 standards in construction projects in Belu Regency.